Ternary positive electrode material and preparation method thereof, positive electrode plate and secondary battery
By combining the LiNiaCobMncM1-a-b-cO2+d core with the NbxN1-xO3-0.5x-y cladding layer in the ternary positive electrode material, the coating layer of the Wadsley-Roth phase was formed, and the problem of poor conductivity of the ternary positive electrode material with medium nickel content was solved. , improves discharge capacity and cycling performance.
Patent Information
- Application Number
- CN202411313597.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
The ternary cathode material with medium nickel content has poor conductivity and high impedance, which affects its capacity performance.
Using a ternary positive electrode material containing LiNiaCobMncM1-a-b-cO2+d core and NbxN1-xO3-0.5x-y cladding layer, the Wadsley-Roth phase cladding layer is formed by calcining treatment, which improves ionic conductivity and electronic conductivity and reduces impedance. .
It effectively improves the discharge capacity and first-time Coulomb efficiency of the ternary positive electrode material, reduces the contact and side reaction between the core and the electrolyte, and improves the circulation performance.
Smart Images

Figure CN119297225A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, and particularly to a ternary cathode material, a preparation method thereof, a cathode pole piece, and a secondary battery. Background Art
[0002] Secondary batteries such as lithium-ion secondary batteries are widely used in fields such as mobile devices, electric vehicles, and energy storage systems. With the continuous improvement of market requirements for lithium-ion secondary batteries, ternary cathode materials with high capacity and high voltage platforms have become a current research hotspot. However, ternary cathode materials with medium nickel content have poor conductivity and high impedance, which affects the capacity of ternary cathode materials. Summary of the Invention
[0003] The present application provides a ternary cathode material, a preparation method thereof, a cathode pole piece, and a secondary battery to reduce the impedance of the ternary cathode material and improve the discharge capacity of the ternary cathode material.
[0004] In a first aspect of the present application, a ternary cathode material is provided, which includes a core and a coating layer covering at least a part of the surface of the core. The core contains a material with the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5≤a≤0.8, 0<b≤0.3, 0.1≤c<0.5, 0≤1-a-b-c≤0.05, -0.05≤d≤0.05, M includes one or more of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, and B. The coating layer contains a material with the chemical formula Nb x N 1-x O 3-0.5x-y , and this material has a Wadsley-Roth phase, where 0.2≤x≤0.8, 0≤y≤0.05, and N includes one or more of W and Mo.
[0005] In some embodiments, the total mass of Nb, Mo, and W in the coating layer accounts for a proportion greater than or equal to 70% of the total mass of Nb, Mo, and W in the ternary cathode material.
[0006] In some embodiments, the total mass ratio of Nb, Mo, and W in the ternary cathode material is 0.05% to 1%.
[0007] In some embodiments, the ternary cathode material includes single crystal particles and / or pseudo single crystal particles.
[0008] In some embodiments, the average diameter of the primary particles of the single crystal particles and / or the pseudo single crystal particles is 1 μm to 3.5 μm.
[0009] In some embodiments, the volume average particle size Dv50 of the ternary cathode material is 2.5 μm to 4.5 μm.
[0010] In some embodiments, the coating layer further contains one or more of Li2WO4, Li2W2O7, LiNbO3, LiNb3O7, Li2MoO4, Li2Mo2O7, and Li2Mo4O 13 among others.
[0011] In a second aspect of the present application, a method for preparing a ternary cathode material is provided, including the following steps:
[0012] Mix a ternary precursor, an M source, and a lithium source, and obtain a core through a first calcination treatment;
[0013] Mix the core with a first additive, the first additive includes a material with the chemical formula Nb x0 N 0 1-x0 O 3-0.5x0-y0 where 0.2 ≤ x0 ≤ 0.8, 0 ≤ y0 ≤ 0.05, N 0 includes one or more of W and Mo, and subject the resulting mixture to a second calcination treatment to form a coating layer on at least part of the surface of the core, thereby obtaining the ternary cathode material; or,
[0014] Prepare a mixed solution containing at least one of a tungsten source and a molybdenum source, a niobium source, and the core, remove the solvent from the mixed solution, and perform a third calcination treatment to form a coating layer on at least part of the surface of the core, thereby obtaining the ternary cathode material;
[0015] The ternary cathode material includes the core and the coating layer, the core contains a material with the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d where 0.5 ≤ a ≤ 0.8, 0 < b ≤ 0.3, 0.1 ≤ c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, M includes one or more of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, and B, and the coating layer contains a material with the chemical formula Nb x N 1-x O 3-0.5x-yThe material has a Wadsley-Roth phase, wherein 0.2≤x≤0.8, 0≤y≤0.05, and N includes one or more of W and Mo.
[0016] In some embodiments, the step of preparing a mixed solution comprising at least one of a tungsten source and a molybdenum source, a niobium source, and the core comprises: mixing the tungsten source and at least one of the molybdenum source, the niobium source, an alkaline solution and the core; optionally, the alkaline solution comprises one or more of aqueous ammonia and a lithium hydroxide solution.
[0017] In some embodiments, the step of removing the solvent from the mixed solution comprises: removing the solvent from the mixed solution by filtering; and / or,
[0018] The solvent in the mixed solution is removed by drying.
[0019] In some embodiments, the first calcination treatment includes a pre-calcination treatment and a calcination treatment performed sequentially, the pre-calcination temperature is 450°C to 650°C, the pre-calcination time is 1h to 4h, the calcination temperature is 800°C to 1000°C, and the calcination time is 6h to 18h.
[0020] In some embodiments, the process conditions of the second calcination treatment and the third calcination treatment independently include: a calcination temperature of 300° C. to 700° C., and a calcination time of 2 h to 24 h.
[0021] In some embodiments, the ternary precursor comprises a chemical formula of Ni a1 Co b1 Mn c1 (OH)2 material, chemical formula is Ni a2 Co b2 Mn c2 The material and chemical formula of C2O4 is Ni a3 Co b3 Mn c3 One or more of the materials of CO3, wherein 0.5≤a1≤0.8, 0 <b1≤0.3,0.1≤c1<0.5,0.5≤a2≤0.8,0<b2≤0.3,0.1≤c2<0.5,0.5≤a3≤0.8,0<b3≤0.3,0.1≤c3<0.5。
[0022] In some embodiments, the M source includes an inorganic compound containing the M element; optionally, the inorganic compound containing the M element includes one or more of an oxide, a hydroxide and a carbonate containing the M element.
[0023] In some embodiments, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3.
[0024] In some embodiments, the tungsten source includes a compound containing a WO chemical bond; optionally, the compound containing a WO chemical bond includes one or more of an oxide containing a tungsten element and tungsten ethoxide.
[0025] In some embodiments, the molybdenum source includes a compound containing a Mo-O chemical bond; alternatively, the compound containing a Mo-O chemical bond includes an oxide containing a molybdenum element.
[0026] In some embodiments, the niobium source includes one or more of a compound containing a Nb—O chemical bond and a chloride containing the niobium element; alternatively, the compound containing a Nb—O chemical bond includes an oxide containing the niobium element.
[0027] The third aspect of the present application provides a positive electrode plate, comprising at least one of the ternary positive electrode material described in the first aspect of the present application and the ternary positive electrode material prepared by the preparation method described in the second aspect of the present application.
[0028] A fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet described in the third aspect of the present application.
[0029] In a fifth aspect of the present application, there is provided an electrical device comprising the secondary battery described in the fourth aspect of the present application.
[0030] Compared with traditional technologies, the above-mentioned ternary cathode materials have at least the following advantages:
[0031] The coating layer of the above-mentioned ternary positive electrode material contains a chemical formula of Nb x N 1-x O 3-0.5x-y The material has a Wadsley-Roth phase. This structure forms a large number of tetrahedral voids, allowing lithium ions to migrate therein, making the material have higher ionic conductivity. Due to the inherently narrow semiconductor band gap of this material, it also has better electronic conductivity. Therefore, the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d The core of the material contains the chemical formula Nb x N 1-x O 3-0.5x-y The use of a coating layer of the material can effectively reduce the impedance of the ternary positive electrode material and improve the discharge capacity and first coulombic efficiency of the ternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] FIG. 1 is a scanning electron microscope (SEM) image of the ternary positive electrode material prepared in Example 2 of the present application.
[0033] FIG. 2 is an X-ray energy spectrum (EDS) Nb element distribution diagram of the ternary positive electrode material prepared in Example 2 of the present application.
[0034] FIG3 is an X-ray energy spectrum (EDS) W element distribution diagram of the ternary positive electrode material prepared in Example 2 of the present application.
[0035] FIG. 4 is a SEM image of the ternary positive electrode material prepared in Comparative Example 2 of the present application.
[0036] FIG5 is an X-ray energy spectrum (EDS) Nb element distribution diagram of the ternary positive electrode material prepared in Comparative Example 2 of the present application.
[0037] FIG6 is an X-ray energy spectrum (EDS) W element distribution diagram of the ternary positive electrode material prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0039] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0040] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0041] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when the range refers to integers, it includes each integer between the minimum and maximum values of the range. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.
[0042] In this application, among the technical features described in an open-ended manner, it includes a closed technical solution composed of the listed features, and also includes an open technical solution containing the listed features.
[0043] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by those skilled in the technical field to which this application belongs. The terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items. The meaning of the term "a variety of" in this application is at least two, such as two, three, etc., unless otherwise specifically defined.
[0044] One embodiment of this application provides a ternary cathode material, including a core and a coating layer covering at least part of the surface of the core. The core contains a material with the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.8, 0 < b ≤ 0.3, 0.1 ≤ c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, M includes one or more of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, and B. The coating layer contains a material with the chemical formula Nb x N 1-x O 3-0.5x-y , and this material has a Wadsley - Roth phase, where 0.2 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.05, and N includes one or more of W and Mo.
[0045] When a is 0.5 - 0.8, the chemical formula of the material in the core is LiNi a Co b Mn c M 1-a-b-c O 2+dThe conductivity of the material is relatively poor compared to the material corresponding to a greater than 0.8, and the impedance is high, which limits its capacity. The coating layer of the above-mentioned ternary positive electrode material contains a chemical formula of Nb x N 1-x O 3-0.5x-y The material has a Wadsley-Roth phase. This structure forms a large number of tetrahedral voids, allowing lithium ions to migrate therein, making the material have higher ionic conductivity. Due to the inherently narrow semiconductor band gap of this material, it also has better electronic conductivity. Therefore, the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d The core of the material contains the chemical formula Nb x N 1-x O 3-0.5x-y The use of a coating layer of the material can effectively reduce the impedance of the ternary positive electrode material, and improve the discharge capacity and first coulomb efficiency of the ternary positive electrode material. The coating layer can effectively reduce the contact between the core and the electrolyte and reduce the occurrence of side reactions, thereby improving the cycle performance of the ternary positive electrode material.
[0046] Specifically, a includes but is not limited to: 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or a range between any two of the foregoing, b includes but is not limited to: 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.28, 0.3 or a range between any two of the foregoing, c includes but is not limited to: 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or a range between any two of the foregoing, d includes but is not limited to: 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or a range between any two of the foregoing Including but not limited to: -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05 or a range between any two of the foregoing, x includes but is not limited to: 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or a range between any two of the foregoing, y includes but is not limited to: 0, 0.01, 0.02, 0.03, 0.04, 0.05 or a range between any two of the foregoing.
[0047] In the present application, the Wadsley-Roth phase is a compound phase having a specific structure, which is composed of edge-sharing octahedrons of the ReO3 structure.
[0048] In a non-limiting manner, the dispersion of Nb, Mo, and W elements in the ternary cathode material can be determined by scanning electron microscopy or energy dispersive spectrometer surface scanning under a spherical aberration transmission electron microscope. The complete dispersion of Nb, Mo, and W elements shows a chemical formula of Nb x N1- x O 3-0.5x-y The chemical formula of the material can also be determined by high-resolution atomic phase analysis under transmission electron microscopy. x N 1-x O 3-0.5x-y The distorted polyhedral structure of the material; thus, the surface chemical formula of the core is determined to be Nb x N 1-x O 3-0.5x-y Successful coating of materials.
[0049] It should be noted that to determine whether a coating material conforms to the above chemical formula Nb x N 1-x O 3-0.5x-y When determining the material, you can normalize the chemical formula of the material before making a judgment.
[0050] In some embodiments, M does not contain less than 500 ppm of any possible impurity elements introduced during production.
[0051] In some embodiments, the total mass of Nb, Mo and W in the coating layer accounts for a proportion of greater than or equal to 70% of the total mass of Nb, Mo and W in the ternary positive electrode material. By controlling the above ratio, Nb, Mo and W are mainly present in the coating layer, thereby improving the ionic conductivity and electronic conductivity of the ternary positive electrode material, which is more conducive to reducing the impedance of the ternary positive electrode material and improving the discharge capacity. Specifically, the above ratio includes but is not limited to: 70%, 75%, 80%, 85%, 90%, 95% or a range between any two of the foregoing.
[0052] In some embodiments, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.05% to 1%. Such a design can improve the ionic conductivity and electronic conductivity of the ternary positive electrode material, which is more conducive to reducing the impedance of the ternary positive electrode material and improving the discharge capacity. Specifically, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material includes but is not limited to: 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range between any two of the foregoing.
[0053] Without limitation, the total mass of Nb, Mo and W in the coating layer and the total mass of Nb, Mo and W in the ternary cathode material can be tested by an inductively coupled plasma spectrometer. For example, the total mass of Nb, Mo and W in the coating layer can be obtained by a constant volume test by immersion in an alkaline solution, and the ternary cathode material can be completely dissolved by an acidic solution, and the total mass of Nb, Mo and W in the ternary cathode material can be obtained by testing.
[0054] In some embodiments, the ternary positive electrode material includes single crystal particles and / or quasi-single crystal particles. Since the average diameter of the primary particles of the single crystal particles or quasi-single crystal particles is smaller than the average diameter of the primary particles of the polycrystalline particles, the electron conduction distance and lithium ion conduction distance of the single crystal particles or quasi-single crystal particles are longer, and their impedance is significantly higher, and the capacity is further limited. Therefore, the ternary positive electrode material including the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d The core of the material contains the chemical formula Nb x N 1- x O 3-0.5x-y The use of a coating layer of the material can further effectively reduce the impedance of the ternary positive electrode material and improve the discharge capacity and first coulombic efficiency of the ternary positive electrode material.
[0055] In the present application, a quasi-single crystal particle refers to a crystal particle formed by the aggregation of several or dozens of single crystal particles, and the number of its grain boundaries is much smaller than that of a polycrystalline particle.
[0056] In some embodiments, the average diameter of the primary particles of the single crystal particles and / or the quasi-single crystal particles is 1 μm to 3.5 μm. The average diameter of the primary particles of the single crystal particles and / or the quasi-single crystal particles is within the above range, which can further effectively reduce the impedance of the ternary positive electrode material and improve the discharge capacity and the first coulombic efficiency of the ternary positive electrode material.
[0057] In some embodiments, the volume average particle size Dv50 of the ternary cathode material is 2.5 μm to 4.5 μm. Specifically, the volume average particle size Dv50 includes but is not limited to: 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm or a range between any two of the foregoing.
[0058] In the present application, the volume average particle size Dv50 of the ternary positive electrode material refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of the sample reaches 50%.
[0059] In some embodiments, the coating layer further comprises Li2WO4, Li2W2O7, LiNbO3, LiNb3O7, Li2MoO4, Li2Mo2O7 and Li2Mo4O 13 One or more of the above. A layer containing a chemical formula of Nb is formed on the surface of the core. x N 1-x O 3-0.5x-yWhen forming a coating layer on a material, it is accompanied by the formation of a compound containing at least one chemical bond among Nb-O, Mo-O, and W-O. For example: Li2WO4, Li2W2O7, LiNbO3, LiNb3O7, Li2MoO4, Li2Mo2O7, and Li2Mo4O 13 One or more of them.
[0060] Another embodiment of the present application provides a method for preparing a ternary cathode material, including the following steps:
[0061] Mix a ternary precursor, an M source, and a lithium source, and obtain a core through a first calcination treatment;
[0062] Mix the core and a first additive. The first additive includes a material with the chemical formula Nb x0 N 0 1-x0 O 3-0.5x0-y0 where 0.2 ≤ x0 ≤ 0.8, 0 ≤ y0 ≤ 0.05, and N 0 includes one or more of W and Mo. Subject the resulting mixture to a second calcination treatment to form a coating layer on at least part of the surface of the core, thereby obtaining a ternary cathode material; or,
[0063] Prepare a mixed solution containing at least one of a tungsten source and a molybdenum source, a niobium source, and the core. Remove the solvent from the mixed solution, and subject it to a third calcination treatment to form a coating layer on at least part of the surface of the core, thereby obtaining a ternary cathode material;
[0064] The ternary cathode material includes a core and a coating layer. The core contains a material with the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d where 0.5 ≤ a ≤ 0.8, 0 < b ≤ 0.3, 0.1 ≤ c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and M includes one or more of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, and B. The coating layer contains a material with the chemical formula Nb x N 1-x O 3-0.5x-y and this material has a Wadsley-Roth phase, where 0.2 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.05, and N includes one or more of W and Mo.
[0065] In the coating layer of the ternary cathode material prepared by the above preparation method, it contains a material with the chemical formula Nb x N 1-x O 3-0.5x-yThe material has a Wadsley-Roth phase. This structure forms a large number of tetrahedral voids, allowing lithium ions to migrate therein, making the material have higher ionic conductivity. Due to the inherently narrow semiconductor band gap of this material, it also has better electronic conductivity. Therefore, the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d The core of the material contains the chemical formula Nb x N 1-x O 3-0.5x-y The coating layer of the material can effectively reduce the impedance of the ternary positive electrode material and improve the discharge capacity and first coulomb efficiency of the ternary positive electrode material. The coating layer can effectively reduce the contact between the core and the electrolyte and reduce the occurrence of side reactions, thereby improving the cycle performance of the ternary positive electrode material. The above preparation method is simple and is conducive to the large-scale production of ternary positive electrode materials.
[0066] Specifically, x0 includes but is not limited to: 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or a range between any two of the foregoing, and y0 includes but is not limited to: 0, 0.01, 0.02, 0.03, 0.04, 0.05 or a range between any two of the foregoing.
[0067] In some embodiments, the step of preparing a mixed solution comprising at least one of a tungsten source and a molybdenum source, a niobium source, and a core comprises: mixing at least one of a tungsten source and a molybdenum source, a niobium source, an alkaline solution, and the core. The alkaline solution is conducive to the dissolution of at least one of a tungsten source and a molybdenum source and a niobium source, thereby facilitating the dissolution of the coating layer with a chemical formula of Nb x N 1-x O 3-0.5x-y In some embodiments, the alkaline solution includes one or more of aqueous ammonia and lithium hydroxide solution.
[0068] In some embodiments, the step of removing the solvent from the mixed solution comprises: removing the solvent from the mixed solution by filtering; and / or,
[0069] The solvent in the mixed solution is removed by drying.
[0070] In the above embodiment, the drying process includes but is not limited to drying under reduced pressure.
[0071] In some embodiments, the step of mixing the core and the first additive comprises: mixing the core, the first additive and the second additive. Optionally, the second additive contains one or more elements of Ni, Co, Mn, Li, Mg, Al, Ti, Zr, Y, Sr, Si, F, La and B.
[0072] In some embodiments, the first calcination treatment includes a pre-calcination treatment and a calcination treatment performed sequentially, the pre-calcination temperature is 450°C to 650°C, the pre-calcination time is 1h to 4h, the calcination temperature is 800°C to 1000°C, and the calcination time is 6h to 18h.
[0073] In some embodiments, the process conditions of the second calcination treatment and the third calcination treatment independently include: a calcination temperature of 300°C to 700°C, and a calcination time of 2h to 24h. The process conditions of the second calcination treatment and the third calcination treatment are independently controlled within the above range, which is conducive to stabilizing the chemical formula Nb x N 1-x O 3-0.5x-y The structure of the material is maintained in a phase favorable for low temperature impedance. Specifically, the calcination temperature includes but is not limited to: 300°C, 400°C, 500°C, 600°C, 700°C or a range between any two of the foregoing, and the calcination time includes but is not limited to: 2h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, 22h, 24h or a range between any two of the foregoing.
[0074] In some embodiments, the process conditions of the second calcination treatment and the third calcination treatment independently include: a calcination temperature of 450° C. to 550° C., and a calcination time of 4 h to 6 h.
[0075] In some embodiments, the first calcination process, the second calcination process, and the third calcination process are each independently performed in an oxygen-containing atmosphere.
[0076] In some embodiments, the ternary precursor comprises a Ni a1 Co b1 Mn c1 (OH)2 material, chemical formula is Ni a2 Co b2 Mn c2 The material and chemical formula of C2O4 is Ni a3 Co b3 Mn c3 One or more of the materials of CO3, wherein 0.5≤a1≤0.8, 0 <b1≤0.3,0.1≤c1<0.5,0.5≤a2≤0.8,0<b2≤0.3,0.1≤c2<0.5,0.5≤a3≤0.8,0<b3≤0.3,0.1≤c3<0.5。
[0077] Specifically, a1, a2, and a3 each independently include but are not limited to: 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or a range between any two of the foregoing, b1, b2, and b3 each independently include but are not limited to: 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.28, 0.3 or a range between any two of the foregoing, c1, c2, and c3 each independently include but are not limited to: 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or a range between any two of the foregoing.
[0078] In some embodiments, the M source includes an inorganic compound containing the M element. Alternatively, the inorganic compound containing the M element includes one or more of an oxide, a hydroxide and a carbonate containing the M element.
[0079] In some embodiments, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3.
[0080] In some embodiments, the tungsten source includes a compound containing a WO chemical bond. Optionally, the compound containing a WO chemical bond includes one or more of an oxide containing a tungsten element and tungsten ethoxide ((C2H5O)5W). Exemplarily, the oxide containing a tungsten element includes but is not limited to WO3, Nb8W9O 47 and Nb4W7O 31 At least one of .
[0081] In some embodiments, the molybdenum source includes a compound containing a Mo-O chemical bond. Alternatively, the compound containing a Mo-O chemical bond includes an oxide containing a molybdenum element. Alternatively, the oxide containing a molybdenum element includes, but is not limited to, Nb2MoO8.
[0082] In some embodiments, the niobium source includes one or more of a compound containing a Nb-O chemical bond and a chloride containing the niobium element. Alternatively, the compound containing a Nb-O chemical bond includes an oxide containing the niobium element. Alternatively, the oxide containing the niobium element includes, but is not limited to: Nb2O5, Nb2WO8, Nb2MoO8, Nb8W9O 47 、Nb4W7O 31 Optionally, the chloride containing niobium element includes but is not limited to: NbCl5.
[0083] Another embodiment of the present application provides a positive electrode plate, including at least one of the above-mentioned ternary positive electrode material of the present application and the ternary positive electrode material prepared by the above-mentioned preparation method of the present application. The above-mentioned positive electrode plate comprises a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, and the positive electrode active layer comprises a positive electrode active material, a conductive agent and a binder. The positive electrode active material comprises at least one of the above-mentioned ternary positive electrode material or the ternary positive electrode material prepared by the above-mentioned preparation method, and the conductive agent and the binder can adopt the conductive agent and the binder commonly used in the technical field.
[0084] Another embodiment of the present application also provides a secondary battery, including the above-mentioned positive electrode plate of the present application. The above-mentioned secondary battery may, for example, include the above-mentioned positive electrode plate, negative electrode plate, electrolyte and separator of the present application. The separator is arranged between the positive electrode plate and the negative electrode plate, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows active ions to pass through. The electrolyte plays the role of conducting active ions between the positive electrode plate and the negative electrode plate. During the charging and discharging process of the secondary battery, the active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate. The present application has no special restrictions on the negative electrode plate, electrolyte and separator, and the negative electrode plate, electrolyte and separator prepared by the commonly used preparation method in the technical field, or the commonly used negative electrode plate, electrolyte and separator in the art can be used.
[0085] In some embodiments, the secondary battery is a lithium ion secondary battery.
[0086] Another embodiment of the present application further provides an electric device, including the secondary battery of the present application. The electric device may include any device or apparatus using the secondary battery as a driving source, such as a mobile phone, a laptop computer, an electric vehicle, a ship, a satellite, an energy storage device, a smart home appliance, etc., but is not limited thereto.
[0087] In order to further illustrate the present application, the technical scheme of the present application is described in detail below in conjunction with specific examples. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0088] Example 1
[0089] The preparation method of the ternary positive electrode material comprises the following steps:
[0090] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0091] (2) Add 1000ppm of the first additive Nb2WO8 powder (Dv50=0.7μm, BET=25m 2 / g)), mixed evenly, and then placed at 550°C in an air atmosphere for 6 hours to form a coating layer on the surface of part of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.074%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0092] Example 2
[0093] The preparation method of the ternary positive electrode material comprises the following steps:
[0094] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm) and Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) is added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0095] (2) Add 2000ppm of the first additive Nb2WO8 powder (Dv50=0.7μm, BET=25m 2 / g), mixed evenly, placed in air atmosphere at 550 ° C, baked for 6 hours, and formed a coating layer on the surface of part of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.5 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.148%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0096] Example 3
[0097] The preparation method of the ternary positive electrode material comprises the following steps:
[0098] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3The molar ratio of the total metal elements in the lithium source Li2CO3 ternary precursor to the lithium element in the lithium source is 1:1.05, and then the M source (1000ppm ZrO2, 1000ppm Sr(OH)2, 500ppm MgO) is added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950rpm / min, and the mixing time is 50min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600℃ for 3h, and then the temperature is increased to 950℃ and roasted for 10h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0099] (2) Add 1000ppm of the first additive Nb2MoO8 powder (Dv50=0.7μm, BET=25m 2 / g), mixed evenly, and then placed in air atmosphere at 550 ° C, baked for 6 hours, to form a coating layer on the surface of part of the core, the coating layer contains a material with a chemical formula of Nb2MoO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 Mo 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.069%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0100] Example 4
[0101] The preparation method of the ternary positive electrode material comprises the following steps:
[0102] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0103] (2) Add 2000 ppm of the first additive Nb2MoO8 powder (Dv50=0.7μm, BET=25m 2 / g), mixed evenly, and then placed in air atmosphere at 550 ° C, baked for 6 hours, to form a coating layer on the surface of part of the core, the coating layer contains a material with a chemical formula of Nb2MoO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 Mo 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.5 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.139%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0104] Example 5
[0105] The preparation method of the ternary positive electrode material comprises the following steps:
[0106] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0107] (2) Under water-free conditions, the core is immersed in an ethanol solution of NbCl5 (niobium source) and (C2H5O)5W (tungsten source), with the mass ratio of the core to the solution being 1:2. The niobium pentachloride and tungsten ethanol in the solution are calculated based on the production of 1000ppm Nb2WO8. Then, deionized water (5% of the mass of the core) is slowly added to the solution system under high-speed stirring, and then the stirring is continued for 10 minutes. After filtration and drying, the obtained solid material is vacuum dried at 50°C for 12 hours, and then calcined at 550°C in an air atmosphere for 6 hours to form a coating layer on a portion of the surface of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.7 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.074%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0108] Example 6
[0109] The preparation method of the ternary positive electrode material comprises the following steps:
[0110] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0111] (2) Under water-free conditions, the core is immersed in an ethanol solution of NbCl5 (niobium source) and (C2H5O)5W (tungsten source), the mass ratio of the core to the solution is 1:2, and the niobium pentachloride and tungsten ethanol in the solution are calculated to generate 2000 ppm Nb2WO8. Then, deionized water (5% of the mass of the core) is slowly added to the solution system under high-speed stirring, and then the stirring is continued for 10 minutes. After filtering and drying, the obtained solid material is vacuum dried at 50°C for 12 hours, and then placed in an air atmosphere at 550°C and calcined for 6 hours to form a coating layer on part of the surface of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.7 μm, the average diameter of the primary particles is 1.8 μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.148%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0112] Example 7
[0113] The preparation method of the ternary positive electrode material comprises the following steps:
[0114] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000ppm ZrO2, 1000ppm Sr(OH)2, 500ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950rpm / min, and the mixing time is 50min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600°C for 3h, and then the temperature is increased to 950°C and roasted for 10h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0115] (2) The core is immersed in an ammonia solution (alkaline solution) of niobium oxide Nb2O5 (niobium source) and tungsten oxide WO3 (tungsten source), the mass ratio of the core to the solution is 8:1, and the niobium oxide and tungsten oxide in the solution are calculated based on the generation of 1000ppm Nb2WO8. The mixture is then dried under reduced pressure for 5 hours under stirring until the solution is completely volatilized. The dried intermediate is placed in an air atmosphere at 550°C and calcined for 6 hours to form a coating layer on a portion of the surface of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.7 μm, the average diameter of the primary particles is 1.8 μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.074%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0116] Example 8
[0117] The preparation method of the ternary positive electrode material comprises the following steps:
[0118] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0119] (2) The core is immersed in an ammonia solution (alkaline solution) of niobium oxide Nb2O5 (niobium source) and tungsten oxide WO3 (tungsten source), the mass ratio of the core to the solution is 8:1, and the niobium oxide and tungsten oxide in the solution are calculated based on the generation of 2000ppm Nb2WO8. The mixture is then dried under reduced pressure for 5 hours under stirring until the solution is completely volatilized. The dried intermediate is placed in an air atmosphere at 550°C and calcined for 6 hours to form a coating layer on a portion of the surface of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.7 μm, the average diameter of the primary particles is 1.8 μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.148%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0120] Example 9
[0121] The preparation method of the ternary positive electrode material comprises the following steps:
[0122] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0123] (2) Add 2000ppm of the first additive Nb2WO8 powder (Dv50=0.7μm, BET=25m 2 / g), mixed evenly, placed in air atmosphere at 500 ° C, baked for 6 hours, and formed a coating layer on the surface of part of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.148%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0124] Example 10
[0125] The preparation method of the ternary positive electrode material comprises the following steps:
[0126] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then the M source (1000ppm ZrO2, 1000ppm Sr(OH)2, 500ppm MgO) is added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950rpm / min, and the mixing time is 50min. After fully mixing, a mixture is obtained. The mixture is placed in an oxygen atmosphere and roasted at 600℃ for 3h, and then the temperature is increased to 950℃ and roasted for 10h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0127] (2) Add 2000ppm of the first additive Nb2WO8 powder (Dv50 = 0.7μm, BET = 25m 2 / g), mixed evenly, placed in air atmosphere at 450 ° C, baked for 6 hours, and formed a coating layer on the surface of part of the core. The coating layer contains a material with a chemical formula of Nb2WO8 (the chemical formula of the material can be written as Nb after normalization). 0.67 W 0.33 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.5 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.148%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0128] Embodiment 11
[0129] The preparation method of the ternary positive electrode material comprises the following steps:
[0130] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0131] (2) Add 2000ppm of the first additive Nb8W9O to the core 47 Powder (Dv50=1μm, BET=20m 2 / g), mixed evenly, and then calcined at 550°C in air atmosphere for 6 hours to form a coating layer on the surface of part of the core. The coating layer contains the chemical formula Nb8W9O 47 The material (the chemical formula of the material can be written as Nb after normalization) 0.47 W 0.53 O 2.76 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.152%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0132] Example 12
[0133] The preparation method of the ternary positive electrode material comprises the following steps:
[0134] (1) The ternary positive electrode material Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0135] (2) Add 2000ppm of the first additive Nb4W7O to the core 31 Powder (Dv50 = 1μm, BET = 20m 2 / g), mixed evenly, and then calcined at 550°C in air atmosphere for 6 hours to form a coating layer on the surface of part of the core. The coating layer contains the chemical formula Nb4W7O 31 The material (the chemical formula of the material can be written as Nb after normalization) 0.36 W 0.64 O 2.82 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the sum of the mass proportions of Nb, Mo and W in the ternary positive electrode material is 0.154%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0136] Embodiment 13
[0137] The preparation method of the ternary positive electrode material comprises the following steps:
[0138] (1) The ternary positive electrode material Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0139] (2) Add 1000 ppm of the first additive Nb4WMoO to the core 16 Powder (Dv50=1 μm, BET=20m 2 / g), mixed evenly, and then calcined at 550°C in air atmosphere for 6 hours to form a coating layer on the surface of part of the core. The coating layer contains the chemical formula Nb4WMoO 16 The material (the chemical formula of the material can be written as Nb after normalization) 0.67 W 0.165 Mo 0.165 O 2.67 ), and the material has a Wadsley-Roth phase, thereby obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.72%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0140] Comparative Example 1
[0141] The preparation method of the ternary positive electrode material comprises the following steps:
[0142] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3(OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000ppm ZrO2, 1000ppm Sr(OH)2, 500ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950rpm / min, and the mixing time is 50min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600°C for 3h, and then the temperature is increased to 950°C and roasted for 10h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0143] (2) The inner core is placed in an air atmosphere at 550° C. and calcined for 6 hours to obtain a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.8 μm, and the average diameter of the primary particles is 1.8 μm.
[0144] Comparative Example 2
[0145] The preparation method of the ternary positive electrode material comprises the following steps:
[0146] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3 (OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0147] (2) Add 2000ppm Nb2O5 powder (Dv50=0.7μm, BET=25 m 2 / g), mixed evenly and placed at 550°C in an air atmosphere, baked for 6h, forming a coating layer on part of the surface of the inner core, the coating layer containing a material with a chemical formula of Nb2O5, and obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6μm, the average diameter of the primary particles is 1.8μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.14%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0148] Comparative Example 3
[0149] The preparation method of the ternary positive electrode material comprises the following steps:
[0150] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3 (OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0151] (2) Add 1000ppm Nb2O5 and 1000ppm WO3 powder (Dv50=0.5~1μm, BET=15~25m 2 / g), mixed evenly and placed at 550°C in an air atmosphere for calcination for 6h, a coating layer is formed on part of the surface of the inner core, the coating layer contains materials with chemical formulas of Nb2O5 and WO3, and a ternary positive electrode material is obtained; the ternary positive electrode material is single crystal particles and / or quasi-single crystal particles, the volume average particle size Dv50 of the ternary positive electrode material is 3.6 μm, the average diameter of the primary particles is 1.8 μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.150%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0152] Comparative Example 4
[0153] The preparation method of the ternary positive electrode material comprises the following steps:
[0154] (1) The ternary precursor Ni 0.60 Co 0.1 Mn 0.3 (OH)2 (Dv50 = 3.2 μm), lithium source Li2CO3 are mixed according to the molar ratio of the total metal elements in the ternary precursor to the lithium element in the lithium source of 1:1.05, and then M source (1000 ppm ZrO2, 1000 ppm Sr(OH)2, 500 ppm MgO) are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained; the mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 h, and then the temperature is increased to 950 ° C and roasted for 10 h to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.598 Co 0.099 Mn 0.299 Zr 0.001 Sr 0.001 Mg 0.002 O2.
[0155] (2) Add 2000ppm WO3 powder (Dv50=0.5~1μm, BET=15~25m 2 / g), mixed evenly and placed at 550°C in an air atmosphere, baked for 6h, forming a coating layer on part of the surface of the inner core, the coating layer containing a material with the chemical formula WO3, and obtaining a ternary positive electrode material; the ternary positive electrode material is a single crystal particle and / or a quasi-single crystal particle, the volume average particle size Dv50 of the ternary positive electrode material is 3.6μm, the average diameter of the primary particles is 1.8μm, the total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.159%, and the total mass of Nb, Mo and W in the coating layer accounts for 100% of the total mass of Nb, Mo and W in the ternary positive electrode material.
[0156] Test Case
[0157] (1) Component test of ternary cathode materials:
[0158] The components of the ternary positive electrode materials prepared in each embodiment or each comparative example were measured using an ICP-AES (inductively coupled plasma atomic emission spectrometry) tester.
[0159] (2) Volume average particle size Dv50 test of ternary positive electrode materials:
[0160] The volume average particle size Dv50 of the ternary positive electrode material prepared in each embodiment or each comparative example is measured using a particle size distribution analyzer.
[0161] (3) Test on the morphology of ternary cathode materials and average diameter of primary particles:
[0162] The morphology of the ternary positive electrode material prepared in each embodiment or each comparative example and the average diameter of the primary particles are tested using SEM, such as a high-resolution field emission scanning electron microscope.
[0163] (4) Distribution test of each element in ternary cathode material:
[0164] The distribution of each element in the ternary positive electrode material prepared in each embodiment or each comparative example was determined by X-ray energy spectrum.
[0165] (5) Battery assembly:
[0166] The ternary positive electrode material prepared in each embodiment or each comparative example was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 95:2.5:2.5, N-methylpyrrolidone was added as a dispersant, and the mixture was ground into a slurry; the slurry was then evenly coated on an aluminum foil, vacuum dried at 120° C. for 10 h, the dried electrode sheet was rolled with a double roller machine, and the aluminum foil was cut with a slicer into a circular electrode sheet with a diameter of 1.2 cm. The loading amount of the active material was controlled at 17 mg / cm 2 Lithium-ion secondary batteries were assembled in an argon atmosphere glove box, where a lithium sheet with a diameter of 1.5 cm was used as the negative electrode, a 12 μm PP / PE film was used as the separator, and 10 μL of 1 mol / L LiPF6 electrolyte was dripped at the interface between the positive electrode sheet, the lithium negative electrode and the electrolyte, and CR2032 button batteries were assembled in an environment with a water partial pressure of ≤0.1 ppm and an oxygen partial pressure of ≤0.1 ppm.
[0167] (6) Battery’s first week discharge capacity and first coulombic efficiency test:
[0168] Lithium-ion secondary battery in the voltage range 2.8V~4.4V vs. Li + / Li range, charge at 0.1C current and discharge at 0.1C current.
[0169] (7) Battery cycle performance test:
[0170] The voltage range of lithium-ion secondary battery at 45°C is 3.0V~4.5V vs. Li + / Li range, charge at 1C current, discharge at 1C current, cycle 50 weeks, capacity retention rate (%) after 50 cycles = discharge specific capacity in the 50th week / discharge specific capacity in the 1st week × 100%.
[0171] (8) Battery DC pulse impedance test:
[0172] Lithium-ion secondary battery in the voltage range 2.8V~4.4V vs. Li + / Li range, charge at 0.1C current, let stand for 20 min, discharge at 1C current for 60s, take the voltage difference before and after 60s discharge and divide by 1C current to get DC pulse resistance.
[0173] The test results of each embodiment and each comparative example are shown in Table 1.
[0174] FIG1 and FIG4 respectively show the SEM images of the ternary positive electrode materials prepared in Example 2 and Comparative Example 2, FIG2 and FIG5 respectively show the X-ray spectrum Nb element distribution diagram of the ternary positive electrode materials prepared in Example 2 and Comparative Example 2, and FIG3 and FIG6 respectively show the X-ray spectrum W element distribution diagram of the ternary positive electrode materials prepared in Example 2 and Comparative Example 2, and the scales in FIG1 to FIG6 are all 2μm. As can be seen from FIG1 and FIG4, the ternary positive electrode materials prepared in Example 2 and Comparative Example 2 are all single crystal particles and / or quasi-single crystal particles, and FIG2 to FIG3 show that the Nb element and the W element in the ternary positive electrode material of Example 2 are uniformly distributed, while the Nb element and the W element in the ternary positive electrode material of Comparative Example 2 corresponding to FIG5 to FIG6 are separately dispersed, and part of the Nb element is agglomerated.
[0175] Table 1
[0176]
[0177] From the data in Table 1, we can see the following:
[0178] Compared with Comparative Examples 1 to 4, the ternary positive electrode materials prepared in Examples 1 to 13 have lower DC pulse resistance and higher first discharge specific capacity, first coulomb efficiency and cycle capacity retention rate, indicating that Examples 1 to 13 contain Nb with Wadsley-Roth phase. x N 1-x O 3-0.5x-yThe coordinated use of the coating layer and the core can reduce the impedance of the ternary positive electrode material and improve the first discharge specific capacity, first coulombic efficiency and cycle performance of the ternary positive electrode material.
[0179] The difference between Comparative Example 1 and Example 2 is that there is no coating layer on the surface of the inner core of the ternary positive electrode material of Comparative Example 1, while a coating layer is formed on the surface of the inner core of the ternary positive electrode material of Example 2. Compared with Comparative Example 1, the first discharge specific capacity of Example 2 is greatly increased, the DC pulse resistance is greatly decreased, the first coulomb efficiency is increased, and the cycle capacity retention rate is greatly increased. This is because the coating layer of the ternary positive electrode material of Example 2 contains Nb2WO8 with Wadsley-Roth phase, which has strong ionic conductivity and electronic conductivity, so that the impedance of the ternary positive electrode material is reduced and the discharge capacity is increased. At the same time, due to its coating on the surface, it also has a certain isolation effect on the electrolyte, and the corresponding cycle retention rate is also improved.
[0180] By comparing Example 2 with Comparative Examples 2 to 4, it can be seen that when the addition amount of coating elements (Nb and / or W) is the same between Example 2 and Comparative Examples 2 to 4, the coating layer formed on the surface of the core of Comparative Examples 2 to 4 contains Nb2O5 and / or WO3, while the coating layer formed on the surface of the core of Example 2 contains Nb2WO8 with Wadsley-Roth phase. Compared with Comparative Examples 2 to 4, the ternary positive electrode material of Example 2 has lower DC pulse resistance and higher first discharge specific capacity, first coulomb efficiency and cycle capacity retention rate, indicating that the Nb with Wadsley-Roth phase in the coating layer of Examples 2 to 4 is more x N 1-x O 3-0.5x-y Compared with simple Nb2O5 and / or WO3, the material has better effect in improving the capacity and reducing the impedance of ternary positive electrode materials.
[0181] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0182] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.
Claims
1. A ternary positive electrode material, characterized in that: It includes a core and a coating layer covering at least part of the surface of the core. The core contains a material with the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.8, 0 < b ≤ 0.3, 0.1 ≤ c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, M includes one or more of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, and B. The coating layer contains a material with the chemical formula Nb x N 1-x O 3-0.5x-y , and this material has a Wadsley - Roth phase, where 0.2 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.05, and N includes one or more of W and Mo.
2. The ternary cathode material according to claim 1, characterized in that: The ternary positive electrode material has at least one of the following characteristics (1) to (2): (1) The total mass of Nb, Mo and W in the coating layer accounts for more than or equal to 70% of the total mass of Nb, Mo and W in the ternary positive electrode material; (2) The total mass proportion of Nb, Mo and W in the ternary positive electrode material is 0.05%~1%.
3. The ternary positive electrode material according to claim 1 or 2, characterized in that: The ternary positive electrode material includes single crystal particles and / or single crystal-like particles; Optionally, an average diameter of primary particles of the single crystal particles and / or the quasi-single crystal particles is 1 μm to 3.5 μm.
4. The ternary positive electrode material according to claim 1 or 2, characterized in that: The ternary positive electrode material has at least one of the following characteristics (1) to (2): (1) The volume average particle size Dv50 of the ternary positive electrode material is 2.5 μm to 4.5 μm; (2) The coating layer also contains Li2WO4, Li2W2O7, LiNbO3, LiNb3O7, Li2MoO4, Li2Mo2O7 and Li2Mo4O 13 One or more of .
5. A method for preparing a ternary positive electrode material, characterized in that: The steps include: The ternary precursor, the M source and the lithium source are mixed and subjected to a first calcination treatment to obtain a core; The core is mixed with a first additive, wherein the first additive comprises a chemical formula of Nb x0 N 0 1-x0 O 3-0.5x0-y0 Materials, where 0.2≤x0≤0.8, 0≤y0≤0.05, N 0 Including one or more of W and Mo, and subjecting the obtained mixture to a second calcination treatment to form a coating layer on at least a portion of the surface of the core to obtain the ternary positive electrode material; or, preparing a mixed solution comprising at least one of a tungsten source and a molybdenum source, a niobium source and the core, removing the solvent in the mixed solution, and performing a third calcination treatment to form a coating layer on at least a portion of the surface of the core to obtain the ternary positive electrode material; The ternary cathode material includes the core and the coating layer. The core contains a material with the chemical formula LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.8, 0 < b ≤ 0.3, 0.1 ≤ c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, M includes one or more of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, and B. The coating layer contains a material with the chemical formula Nb x N 1-x O 3-0.5x-y , and this material has a Wadsley-Roth phase, where 0.2 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.05, and N includes one or more of W and Mo.
6. The preparation method according to claim 5, characterized in that: The step of preparing a mixed solution containing at least one of a tungsten source and a molybdenum source, a niobium source and the core comprises: mixing the tungsten source and at least one of the molybdenum source, the niobium source, an alkaline solution and the core; optionally, the alkaline solution comprises one or more of aqueous ammonia and a lithium hydroxide solution.
7. The preparation method according to claim 5 or 6, characterized in that: The step of removing the solvent from the mixed solution comprises: removing the solvent from the mixed solution by filtering; and / or, The solvent in the mixed solution is removed by drying.
8. The preparation method according to claim 5 or 6, characterized in that: The preparation method meets at least one of the following conditions (1) to (8): (1) The first calcination treatment includes a pre-calcination treatment and a calcination treatment performed in sequence, the pre-calcination temperature is 450°C to 650°C, the pre-calcination time is 1h to 4h, the calcination temperature is 800°C to 1000°C, and the calcination time is 6h to 18h; (2) The process conditions of the second calcination treatment and the third calcination treatment independently include: a calcination temperature of 300° C. to 700° C. and a calcination time of 2 h to 24 h; (3) The ternary precursor includes a chemical formula of Ni a1 Co b1 Mn c1 (OH)2 material, chemical formula is Ni a2 Co b2 Mn c2 The material and chemical formula of C2O4 is Ni a3 Co b3 Mn c3 One or more of the materials of CO3, wherein 0.5≤a1≤0.8, 0 <b1≤0.3,0.1≤c1<0.5,0.5≤a2≤0.8,0<b2≤0.3,0.1≤c2<0.5,0.5≤a3≤0.8,0<b3≤0.3,0.1≤c3<0.5; (4) The M source includes an inorganic compound containing the M element; optionally, the inorganic compound containing the M element includes one or more of an oxide, a hydroxide and a carbonate containing the M element; (5) The lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3; (6) The tungsten source includes a compound containing a WO chemical bond; optionally, the compound containing a WO chemical bond includes one or more of an oxide containing a tungsten element and tungsten ethoxide; (7) The molybdenum source includes a compound containing a Mo-O chemical bond; optionally, the compound containing a Mo-O chemical bond includes an oxide containing the molybdenum element; (8) The niobium source comprises one or more of a compound containing a Nb—O chemical bond and a chloride containing the niobium element; optionally, the compound containing a Nb—O chemical bond comprises an oxide containing the niobium element.
9. A positive electrode sheet, characterized in that: It comprises at least one of the ternary positive electrode materials described in any one of claims 1 to 4 and the ternary positive electrode materials prepared by the preparation method described in any one of claims 5 to 8.
10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.